The Effectiveness of Islamic Capital Market Securities in Supporting MSMEs Working Capital Financing - Fera Widyanata; Ahmad Syathiri; Nia Meitisari; Asfeni Nurullah (Department of Development Economics, Universitas Sriwijaya, 2023)
This study was undertaken to determine how effective Islamic Capital Market Securities, namely the issuance of subordinated sukuk and others sukuk in Islamic banking, are on the quantity of working capital financing distribution to MSMEs in Indonesia. By using monthly time series secondary data and multiple linear regression analysis techniques, it was found that the issuance of subordinated sukuk and others sukuk had a significant positive effect on increasing the quantity of working capital financing distribution to MSMEs. It can be concluded that the policy of Islamic banking to issue Islamic Capital Market Securities effectively supports the increase in the working capital of MSMEs.